Penerapan Model Pembelajaran Problem Based Learning (Pbl) Dalam Mata Pelajaran Bahasa Indonesia Bagi Siswa Kelas V SD GMIM 24 Manembo-Nembo - Merentek, Risal M.; Aimbu, Freiske Cicilia; Wullur, Mozes M. (Peneliti.net, 2024)
This research aims to analyze and describe the application of the problem based learning model in Indonesian language subjects for fifth grade students at SD GMIM 24 Manembo-nembo. The research method used is qualitative, with research data collected by observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. To test the validity of the data, data triangulation techniques were used. The results of the research show that before carrying out the learning process the teacher first prepares a learning plan in the form of a lesson plan which includes a learning model that is suitable for application in the material to be taught to achieve the learning objectives. In implementing the teaching and learning process the teacher must be able to take control of the class so that the teaching and learning process runs well. The learning outcomes of class V students are quite good, but with the implementation of the problem based learning model, especially in Indonesian language subjects, the learning outcomes of class V students have improved a lot. The increase in student learning outcomes can be seen from the evaluation results. There is an increase in students' understanding and understanding. learning material, which is characterized by an increase in learning completeness through achieving the Minimum Completeness Criteria (KKM), this is because the teacher has succeeded in choosing the application of a learning model that is suitable and appropriate to the students' circumstances.